Infection Rate of Sarcocystis Spp. of the Intermediate Hosts in Iraq from 1999-2020 AD. (NTU Journal of Agriculture and Veterinary Science, 2022)
Sarcocysts spp. are protozoal parasites that are widly spread in mammals, reptiles and birds , the disease they cause is called Sarcocystosis.The aim of this review to knowledge the infection rate and species of Sarcocystis. in intermediate hosts in the provinces of Iraq, and the areas that haven't been register it till now.Collected 30 research puplished about Sarcocystis spp. infection intermadiat hosts in Iraq. Ten species determinated in some intermedaite hosts in Iraq only are: S.tenella, S. arieticanis, S. gigantean , S.ovicanis, S.capricanis, S. caprifelis, S. moulei, S. cruzi, S. cameli and S.fusiformis. No pupulation studies aboutSarcocystis in seven of Iraqi provinces are: Kurkuk , Salah ad Din, Diyala, Wasit, Al-Najef Al-Ashraf, Dhi Qar and Al-Muthanna.The infection rate ranged from 0.1% in Missan in water buffalo to 100% in several animals in many of Iraqi provinces.Key words :Sarcocysts, Review Article, intermedaite hosts, Iraq.